2021
DOI: 10.1021/acsomega.0c05925
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of a Novel Copper Nanozyme for Efficient Dye Degradation

Abstract: In this study, a novel copper nanozyme (CNZ) was synthesized by a mild way and characterized by scanning electron microscopy and Fourier transform infrared spectroscopy (FTIR). The as-fabricated CNZ exhibited typical peroxidase activity toward 2, 2′-azinodi-(3-ethylbenzthiazoline)-6-sulfonate. We successfully applied CNZ for the degradation of methyl orange pollutants. Under the optimum conditions (pH, 3.0; T, 60 °C; H2O2 concentration, 200 mM; dosage of CNZ, 8 mg), 93% of the degradation rate could be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The results showed that when the temperature increased from 20 °C to 60 °C, the activity of the CNZ nanozyme improved correspondingly. 143 Similarly, Wang et al found that 100 °C was optimal for the degradation and detection of phenolic pollutants by a CH-Cu nanozyme. 139 5.3.…”
Section: Environmental Science: Nano Critical Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…The results showed that when the temperature increased from 20 °C to 60 °C, the activity of the CNZ nanozyme improved correspondingly. 143 Similarly, Wang et al found that 100 °C was optimal for the degradation and detection of phenolic pollutants by a CH-Cu nanozyme. 139 5.3.…”
Section: Environmental Science: Nano Critical Reviewmentioning
confidence: 98%
“…They found that CNZ with excellent reusability and storage stability could well-degrade methyl orange with a degradation rate of about 93%. 143…”
Section: The Removal Of Organic Pollutants By Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl orange is a typical dye in industrial wastewater selected as a typical dye pollutant because it is not easily degraded. CNZ was applied to the degradation of methyl orange pollutants [ 160 ]. At a high temperature of 60 °C and pH value of 3.93%, the degradation rate can be obtained in less than 10 minutes.…”
Section: Environmental Managementmentioning
confidence: 99%
“…Thanks to the rapid development of nanotechnology, many nanomaterials with enzyme-like activities have been constructed. These nanomaterials include nanosheets, , metal–organic frameworks, , superparamagnetic nanoarchitectures, two-dimensional metal azolate framework nanosheets, layered double hydroxides, noble metal nanoparticles, transition metal oxides, transition metal sulfides, carbon-based nanomaterials, and so on. Since the concept of nanomaterials was proposed, there have been hundreds of groups conducting research and development on nanomaterials and confirmed their enzyme-like activities.…”
mentioning
confidence: 99%